The copper-transporting capacity of ATP7A mutants associated with Menkes disease is ameliorated by COMMD1 as a result of improved protein expression - Vonk, Willianne I. M. (SP Birkhäuser Verlag Basel, 2011)
Menkes disease (MD) is an X-linked recessive disorder characterized by copper deficiency resulting in a diminished function of copper-dependent enzymes. Most MD patients die in early childhood, although mild forms of MD have also been described. A diversity of mutations in the gene encoding of the Golgi-resident copper-transporting P(1B)-type ATPase ATP7A underlies MD. To elucidate the molecular consequences of the ATP7A mutations, various mutations in ATP7A associated with distinct phenotypes of MD (L873R, C1000R, N1304S, and A1362D) were analyzed in detail. All mutants studied displayed changes in protein expression and intracellular localization parallel to a dramatic decline in their copper-transporting capacity compared to ATP7A the wild-type. We restored these observed defects in ATP7A mutant proteins by culturing the cells at 30°C, which improves the quality of protein folding, similar to that which as has recently has been demonstrated for misfolded ATP7B, a copper transporter homologous to ATP7A. Further, the effect of the canine copper toxicosis protein COMMD1 on ATP7A function was examined as COMMD1 has been shown to regulate the proteolysis of ATP7B proteins. Interestingly, in addition to adjusted growth temperature, binding of COMMD1 partially restored the expression, subcellular localization, and copper-exporting activities of the ATP7A mutants. However, no effect of pharmacological chaperones was observed. Together, the presented data might provide a new direction for developing therapies to improve the residual exporting activity of unstable ATP7A mutant proteins, and suggests a potential role for COMMD1 in this process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00018-011-0743-1) contains supplementary material, which is available to authorized users.